Accounting and Information Systems in Irish Family SME: Professionalisation Effects - Martin Quinn; Peter Cleary; Catherine Batt; Pall Rikhardsson (Journal of Accounting and Management Information Systems (JAMIS), 2021)
Research Question - Does the use of IS in family businesses differ significantly from non-family businesses? Does professionalisation of accountants positively impact the use of IS, and is there a difference between family and non-family businesses? Motivation - Research indicates family businesses have more limited implementation and use of information systems (IS) coupled with less accounting and control. As accounting is a primary user of IS, this paper explores if professionalisation of accounting may explain such reported differences in IS use. Idea - This study tests two hypotheses around IS use and professionalisation of accounting. Using a more refined measure of professionalisation of accounting than previous. Data - Data was collected from a survey of CFOs in a country with a strong family business tradition and strong professional accounting bodies. A response rate of 30% was achieved. Tools - A Mann-Witney test coupled with binary and multi-nominal regressions were used to test the hypotheses. Findings - Although professional accountants' presence is a significant explanatory variable, the results show no significant difference in IS use between family and non-family-owned firms. However, contrary to similar studies in countries without strong professional accounting bodies, the analysis suggests that professionalisation is a significant explanatory factor in the similarities found. Contribution - By applying a more refined measure of professionalisation of accounting, this study provides a useful basis for further exploration of the professionalisation of the accounting function in family firms and links to IS use.
Keywords: M41; 650; information systems (IS); accounting; family businesses; professionalisation